2006
DOI: 10.1590/s0074-02762006000300022
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Colombian Plasmodium falciparum isolates to 4-aminoquinolines and the definition of amodiaquine resistance in vitro

Abstract: There are wide variations in the threshold used to define in vitro resistance of Plasmodium falciparum to amodiaquine (AQ), probably due to differences in methodology and interpretation. In vitro susceptibility data of Colombian P. falciparum strains to AQ and N-desethylamodiaquine is used to illustrate the need to standardized methodologies and compare inhibitory concentrations, instead of resistant/susceptible phenotypes, when studying the mechanisms of resistance to AQ and monitoring drug susceptibility tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Resistance to AQ and its metabolite DEAQ has been linked to mutations in Pfmdr1 [11], [12]. Whereas resistance to AQ has been extensively reported in South America [13], [14], this drug has remained relatively effective in Africa, especially as a viable partner drug for ART [15]. The selection by the AL combination for Pfmdr1 alleles has recently been observed [16].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to AQ and its metabolite DEAQ has been linked to mutations in Pfmdr1 [11], [12]. Whereas resistance to AQ has been extensively reported in South America [13], [14], this drug has remained relatively effective in Africa, especially as a viable partner drug for ART [15]. The selection by the AL combination for Pfmdr1 alleles has recently been observed [16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated consensus on the thresholds to define resistance to N- 18 . The same study maintains that understanding the mechanism of resistance to amodiaquine is useful in the design of new drugs, particularly 4-aminoquinoline derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…AQ is a more active antimalarial then DEAQ, with half-maximal inhibitory concentration (IC 50 ) values 2-8-fold lower [27,42,43]. The little information available shows that the C max of AQ is relatively low -approximately 30 nM (600 mg dose) - [44], falling anyway inside the in vitro IC 50 values of a significant fraction of field analyzed AQ sensitive parasites [41,[45][46][47][48][49].…”
Section: Can Cyp2c8 Polymorphisms Influence Amodiaquine Regimens Effimentioning
confidence: 99%